Cost-effectiveness of catheter ablation versus medical therapy for the treatment of atrial fibrillation in the United Kingdom. (24th May 2021) - Leung, L; Imhoff, RJ; Frame, D; Mallow, PJ; Goldstein, L; Taylor, H; Gallagher, MM
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): This research study was funded by Biosense Webster, Inc. Dr Leung has received research support from Attune Medical (Chicago, IL) towards a research fellowship at St. George"s University of London. The authors have no other relevant affiliations or financial involvement with any organization or entity with a financial interest in or financial conflict with the subject matter or materials discussed in the manuscript apart from those disclosed. Background: Randomised data on patient-related outcomes comparing catheter ablation to medical therapy for the treatment of atrial fibrillation (AF) have shown the effectiveness of catheter ablation. Ablation versus medical therapy should also be analysed from a health economics perspective to achieve optimal healthcare resource allocation. Purpose: To determine the cost effectiveness of catheter ablation compared to medical therapy for the treatment of atrial fibrillation, from the perspective of the UK National Health Service. Methods: A patient-level Markov health-state transition model was used to conduct a cost utility analysis comparing catheter ablation and medical therapy for the treatment of AF. A systematic review and meta-analysis of catheter ablation treatment versus medical therapy (rhythm and/or rate control drugs) was conducted to enable comparison of AF recurrence between treatment groups utilising the model. Additional model parameters were established based upon a best-evidence review of the literature. The model simulated care delivered from a secondary care perspective. Total patients simulated in this model over a lifetime were 250, 000, with patients entering the model at age 64. Only previously treated AF patients were included, including those with concomitant heart failure. A separate scenario analysis was conducted to determine the cost effectiveness specifically in the cohort of patients with AF and heart failure. Main outcomes measures: Incremental cost-effectiveness ratio (ICER) and average total expected costs and quality-of-life years (QALYs) incurred over the lifetime of a patient. AF recurrence, complications and cardiovascular adverse events were compared over the total duration inside the model. Results: In the base case analysis, catheter ablation resulted in a favourable ICER of £8, 614 per additional QALY gained when compared to medical therapy, well below the national Willingness-to-Pay threshold of £20, 000. Catheter ablation was associated with an expected increase of 1.01 QALYs, while adding an additional cost £8, 742 over a patient's lifetime. The cost-effectiveness of catheter ablation was improved in the heart failure sub-group analysis, with an ICER of £6, 438. A significantly greater proportion of patients in the medical therapy group failed rhythm control at any stage compared to catheter ablation (72% vs 24%) and at a faster rate (median time to treatment failure: 3.8 vs 10 years). Conclusion: Catheter ablation appears to be a highly cost-effective treatment for atrial fibrillation, compared to medical therapy, from the perspective of the UK National Health Service. With low rates of adverse events and superiority in achieving rhythm control, AF ablation services should be prioritised with appropriate allocation of healthcare resources.